Survival Outcomes in Male Breast Cancer – A Single Institution Experience - Nisha Hariharan (Asian Pacific Journal of Cancer Care, 2018)
Introduction: Male breast cancer is an uncommon entity. Due to the scarce numbers, treatment protocolshave largely been extrapolated from available evidence for female breast cancers. Methods: We analysed the clinicopathological features and survival outcomes for male breast cancer patients treated at our institute between January 2010 and June 2016. Results: Of the 5534 women treated at our institute, we screened 40 male breast cancers of whom 33 had available follow up data and were included in the present analysis. Male breast cancer constituted 0.7% of all breast cancers. The median age was 60 years and the median tumor size was 3cm with 66% of patients having nodal disease at presentation. Invasive ductal carcinoma was the most common histology and 97% were hormone receptor positive. Most of the patients (87.8%) underwent an upfront modified radical mastectomy. With a median follow up of 36 months, 10 patients experienced recurrences all of which were distant metastasis (3 to the bone, 1 to the brain, and 6 had visceral metastasis). Of these, 7 patients succumbed to the disease. The 3-year overall survival was 78.7 %. Conclusion: Male breast cancer is a rare clinical entity and current treatment guidelines follow those for women. Due to the lack of awareness, men often present to clinics at an advanced stage. Social support targeted at improving awareness and access to treatment could improve outcomes in this cohort.